2014
DOI: 10.4103/2141-9248.129058
|View full text |Cite
|
Sign up to set email alerts
|

Computer use and vision-related problems among university students in Ajman, United Arab Emirate

Abstract: Background:The extensive use of computers as medium of teaching and learning in universities necessitates introspection into the extent of computer related health disorders among student population.Aim:This study was undertaken to assess the pattern of computer usage and related visual problems, among University students in Ajman, United Arab Emirates.Materials and Methods:A total of 500 Students studying in Gulf Medical University, Ajman and Ajman University of Science and Technology were recruited into this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

25
150
3
22

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(221 citation statements)
references
References 13 publications
25
150
3
22
Order By: Relevance
“…Another relevant finding was that girls had 271% more complaints and were 15.61 times more prone to reporting tension headache. Shantakumari et al 22 have also observed that females had 78% more chance of developing headache. Albers et al 19 have reported that from 22 studies on prevalence of primary headache between genders, 15 have reported higher values for females.…”
Section: Discussionmentioning
confidence: 96%
“…Another relevant finding was that girls had 271% more complaints and were 15.61 times more prone to reporting tension headache. Shantakumari et al 22 have also observed that females had 78% more chance of developing headache. Albers et al 19 have reported that from 22 studies on prevalence of primary headache between genders, 15 have reported higher values for females.…”
Section: Discussionmentioning
confidence: 96%
“…Kumah et al (2016) in a study tested the knowledge of respondents regarding computer ergonomics and found that most (70%) of the workers acknowledged not having knowledge of ergonomics related to computer use practices. Shantakumari et al (2012) in a study also reported that only 44 % students were aware of computer ergonomics. In the present study also students were questioned about their knowledge of work behavior while using computer/laptop and the results (Table 2) reveal that majority (65 %) of the girls considered adjustable height of table and chair as very important whereas, majority of the boys (51.66 %) considered it somewhat important.…”
Section: Methodsmentioning
confidence: 96%
“…Shantakumari et al, reported that the students were facing symptoms due to improper viewing distances from computer screen, filters not being placed on the screens and using computer without taking frequent breaks and some of them prevented by taking breaks, Using of screen filters [19].…”
Section: Discussionmentioning
confidence: 99%